Cardiac output monitoring using transthoracic echocardiography in children after cardiac surgery-an observational study of feasibility and concordance with transpulmonary thermodilution. (14th October 2021) - Guha Niyogi, S; Kumar, B; Puri, G D; Negi, S; Mishra, A K; Thingnam, S K S
Abstract: Background: Transthoracic echocardiography (TTE) is commonly used after pediatric cardiac surgery to monitor cardiac function and adequacy of surgery; however it depends on the availability of good echo window and operator skill [1]. Transpulmonary thermodilution (TPTD) is feasible along with calibrated continuous cardiac output measurement in children but seldom used due to cost and the need for a specialized catheter [2]. We hypothesized that TTE would be as good as TPTD, but limited in feasibility following pediatric cardiac surgery. Hence, the concordance, agreement as well as feasibility and trending of cardiac output monitoring by TTE was compared against a reference TPTD method in real-world usage in children after congenital heart surgery. Methods: This was a secondary analysis of data from a previously registered and conducted study in our unit. TPTD monitoring was instituted in children undergoing congenital heart disease repair on cardiopulmonary bypass with a 3F femoral arterial cannula and a central venous injectate temperature sensor. Cardiac output was also measured by transthoracic echocardiography by measurement of the left ventricular outflow tract (LVOT) diameter, LVOT velocity time integral (VTI) and the heart rate as previously described [3, 4]. Measurements were taken after arrival in the ICU, and every 12 hours till after extubation. Correlation, Bland-Altman analysis and polar analysis was done for cardiac output measured by TPTD and TTE. Results: TTE and TPTD measurements of cardiac output correlated well (Pearson's correlation coefficient 0.94; 95% CI 0.90–0.96) (Fig. 1A). Bland Altman analysis showed a mean bias of 0.15 l/min and upper and lower limits of agreement of 0.81 and −0.51 l/min respectively (Fig. 1B). Cardiac output measurement by TTE was possible in 72 instances while TPTD allowed measurement in all 113 instances. Hence, TTE was not feasible in 41 instances across 14 patients, including 19 instances in acyanotic and 22 instances in cyanotic patients. Polar analysis revealed acceptable trending. Conclusions: TTE derived cardiac output demonstrated good correlation, minimal bias and narrow limits of agreement versus TPTD, and was feasible in most cases. This suggests TTE is an acceptable cardiac output measurement modality post pediatric cardiac surgery, as in adults [5]. TPTD-based continuous cardiac output monitoring might have a complementary role in pediatric cardiac critical care, particularly in high risk cases. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Institutional Special Research Grant from Postgraduate Institute of Medical Education and Research, Chandigarh, India.